Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1097/opx.0000000000000269
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation of Retinal Thickness in Healthy Subjects

Abstract: The Spectralis SD-OCT retinal thickness measurements showed a small but statistically significant diurnal variation in nasal and inferior subfields toward smaller values in the evening. However, the overall change is close to the instrument's resolution and repeatability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…Previous studies have assessed diurnal changes in retina thickness using SD-OCT. Jo et al 21 measured total retina thickness at two time points and reported no diurnal variations. Ashraf and Nowroozzadeh 22 measured retina thickness at three time points over 12 hours and reported greater macular thickness at 7 hours only in the inferior region. Ahn et al 16 found significant diurnal variation in total retina thickness for some regions, with no variation in outer retina thickness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have assessed diurnal changes in retina thickness using SD-OCT. Jo et al 21 measured total retina thickness at two time points and reported no diurnal variations. Ashraf and Nowroozzadeh 22 measured retina thickness at three time points over 12 hours and reported greater macular thickness at 7 hours only in the inferior region. Ahn et al 16 found significant diurnal variation in total retina thickness for some regions, with no variation in outer retina thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Diurnal changes in retina thickness in adult subjects have also been evaluated using SD-OCT; however, results have been conflicting. Previous studies have assessed retina thickness over a 10- to 12-hour time period and reported no diurnal variations in total retina thickness, 9 , 19 , 21 diurnal variations in only two quadrants for total retina thickness, 22 or diurnal variations in only the outer retina. 9 A recent study found that the macular region did not undergo diurnal thickness changes, but some quadrants of more peripheral regions underwent thickness changes across 24 hours.…”
mentioning
confidence: 96%
“…Although circumpapillary RNFL thickness is generally considered to have excellent repeatability, thinning of the RNFL from morning to evening has previously been reported for healthy individuals. 29,30 Overall, the magnitude of this change is small and less than the calculated repeatability for RNFL thickness at the 3.5 mm diameter commonly used for clinical evaluation. Similar to the present study, several previous studies have reported excellent repeatability for BMO-MRW when scans are obtained within short succession.…”
Section: Discussionmentioning
confidence: 85%
“…However, we would like to raise some methodological concerns from an ophthalmologic point of view. Firstly, the authors did not clarify if they performed the OCT examination at the same part of the day for both the patients with MD and healthy subjects; in this regard, it has been reported that retinal thickness can be subjected to small but statistically significant diurnal variations 2,3 . Thus, we deem that more precise information about the timing of the examination should have been provided, especially not neglecting the possible difference between the examined and the control group.…”
Section: Accepted Manuscriptmentioning
confidence: 99%